2017
DOI: 10.1016/j.neo.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Cycle Inhibitors p21 Cip1 and p27 Kip1 Control Proliferation but Enhance DNA Damage Resistance of Glioma Stem Cells

Abstract: High-grade gliomas are the most prevalent and lethal primary brain tumors. They display a hierarchical arrangement with a population of self-renewing and highly tumorigenic cells called cancer stem cells. These cells are thought to be responsible for tumor recurrence, which make them main candidates for targeted therapies. Unbridled cell cycle progression may explain the selective sensitivity of some cancer cells to treatments. The members of the Cip/Kip family p21Cip1 and p27Kip1 were initially considered as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…It is well known that p27 acts as a cell cycle repressor 17 . Induction of p27 can impair cell cycle progression and render cells more susceptible to DNA damage 18 . Therefore, the growth-suppressive activity of LINC00963 is causally linked to alteration of cell-cycle regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that p27 acts as a cell cycle repressor 17 . Induction of p27 can impair cell cycle progression and render cells more susceptible to DNA damage 18 . Therefore, the growth-suppressive activity of LINC00963 is causally linked to alteration of cell-cycle regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…p21 is indispensable for maintaining self-renewal of leukemia stem cells [88], and it is able to inhibit oncogene-induced EMT and breast tumor stem cells in transgenic mice [101]. In a study with five patient-derived glioma stem cell-enriched cell lines, the authors have reported that p21 and p27 operate both as tumor suppressors, limiting cell proliferation, but also as oncogenes, conferring cell resistance to DNA damage and developing drug resistance [189]. Further investigations are mandatory to delineate if suppression of p21 serves as a therapeutic target, though its antisense therapy radiosensitizes human colon cancer cells [190] and glioma cells [191] to apoptosis.…”
Section: Translating In Tumor Therapymentioning
confidence: 99%
“…Sinomenine promotes p53 expression and acetylation, leading to G0/G1 cell cycle arrest and apoptosis 4 . P21 acts as a tumor suppressor gene to stop the cell cycle and limit cell proliferation 5 . Furthermore, 40‐50% of gliomas have PTEN inactivation, leading to the abnormal activation of PI3K activity and downstream signaling pathways 6 .…”
Section: Introductionmentioning
confidence: 99%